1979
DOI: 10.1002/ajmg.1320030110
|View full text |Cite
|
Sign up to set email alerts
|

Inherited interstitial del(Xp) with minimal clinical consequences: With a note on the location of genes controlling phenotypic features

Abstract: In a routine cytogenetic investigation of the outpatients of a hospital for the mentally retarded, a 26-year-old women with a presumptive interstitial deletion of the short arm of one of the X chromosomes was found. The same aberration was found in her phenotypically normal mother and in one of her four sisters, all phenotypically normal. By GTG- and QFQ-banding methods, the deletion was interpreted to involve the entire band Xp21 and adjacent parts of p11 and p22. The karyotype is written 46,X,del(X)(pter lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Hoo (27) suggested that deletions distal to p11 are asymptomatic. This suggestion was supported by Herva et al (25). However, Goldman et al (26), noted that only the size of the deletion in an X chromosome cannot predict whether a Turner patient menstruated or not.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Hoo (27) suggested that deletions distal to p11 are asymptomatic. This suggestion was supported by Herva et al (25). However, Goldman et al (26), noted that only the size of the deletion in an X chromosome cannot predict whether a Turner patient menstruated or not.…”
Section: Discussionmentioning
confidence: 88%
“…The karyotype of the 1st pair was del(X)(p211) and the second had del(X)(p114). A woman with del(Xp), who marries a normal man, may have a daughter with the same karyotype (with a probability of one in three) but not a son because a combination of Y and del (Xp) is fatal (25). In some families, mothers with 45,X/ 46,X,del(X) gave birth to daughters with a single cell line of del(Xp) (21,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In female patients affected by the above-  mentioned rearrangement, no normal pubertal spurt is observed. The presence of certain small morphological abnormalities plus subtle radiological symptoms are significant markers, indicating the necessity of genetic studies [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…After transfer, the filters were rinsed in 4X SSC, and baked for 2 h at 80'C. Prehybridization was performed in a mixture containing 50% formamide, 4X SSC, 8% dextran sulfate, lOx Denhardt's solution (15), 25 gg/ml denatured salmon DNA, 100 jsg/ml transfer RNA (tRNA), 1 (28,29). One of these females had decreased T helper lymphocytes but normal numbers ofB cells.…”
Section: Introductionmentioning
confidence: 99%